2011
DOI: 10.2147/ijn.s14613
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced reduction in cell viability by hyperthermia induced by magnetic nanoparticles

Abstract: Colloidal suspensions of iron oxide magnetic nanoparticles are known to dissipate energy when exposed to an oscillating magnetic field. Such energy dissipation can be employed to locally raise temperature inside a tumor between 41°C and 45°C (hyperthermia) to promote cell death, a treatment known as magnetic fluid hyperthermia (MFH). This work seeks to quantify differences between MFH and hot-water hyperthermia (HWH) in terms of reduction in cell viability using two cancer cell culture models, Caco-2 (human ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Rodriguez-Luccioni et al (2011) showed in vitro that heating with MNPs resulted in greater decrease in cell viability over hot water hyperthermia under similar time-temperature conditions. [35] Lee et al (2011) showed that much lower doses of cisplatin are effective in combination with MFH, enhancing the anticancer activity of cisplatin more than hot water bath hyperthermia. [14a] Alvarez-Berrios et al (2013) demonstrated that fluidization of the cell membrane occurs due to heating with MNPs, which enhances drug uptake [15] and that MFH has synergy with cisplatin even in resistant cell lines.…”
Section: Can Nanoscale Thermal Phenomena In the Vicinity Of Magnetmentioning
confidence: 99%
“…Rodriguez-Luccioni et al (2011) showed in vitro that heating with MNPs resulted in greater decrease in cell viability over hot water hyperthermia under similar time-temperature conditions. [35] Lee et al (2011) showed that much lower doses of cisplatin are effective in combination with MFH, enhancing the anticancer activity of cisplatin more than hot water bath hyperthermia. [14a] Alvarez-Berrios et al (2013) demonstrated that fluidization of the cell membrane occurs due to heating with MNPs, which enhances drug uptake [15] and that MFH has synergy with cisplatin even in resistant cell lines.…”
Section: Can Nanoscale Thermal Phenomena In the Vicinity Of Magnetmentioning
confidence: 99%
“…MFH has also been shown to kill cells faster as compared to traditional hyperthermia methods, which can play an essential role in reducing the therapy administration time for cancer treatment [4]. MFH can reduce side effects in patients while amplifying treatment of cancer using superparamagnetic NPs, which can be specifically targeted using antibodies or peptide sequences [5,6] and directed to cancerous tissue through the enhanced permeation and retention (EPR) effect [7].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of energy has been used, including microwaves and radio waves (Gazelle et al, 2000; Seki et al, 1999), magnetic heating (Lee et al, 2011; Rodriguez-Luccioni et al, 2011), and ultrasound (Jolesz and Hynynen, 2002). Regional hyperthermia (e.g., hyperthermic intraperitoneal chemotherapy [HIPEC] heated to 42°C), theoretically enables direct contact between tumor cells and the chemotherapeutic agent to control residual microscopic disease (Jinny Ha, 2012).…”
Section: Introductionmentioning
confidence: 99%